2021
DOI: 10.1016/j.ejso.2021.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative intensive care unit stay after minimally invasive esophagectomy shows large hospital variation. Results from the Dutch Upper Gastrointestinal Cancer Audit

Abstract: Introduction: The value of routine intensive care unit (ICU) admission after minimally invasive esophagectomy (MIE) has been questioned. This study aimed to investigate Dutch hospital variation regarding length of direct postoperative ICU stay, and the impact of this hospital variation on short-term surgical outcomes. Materials and methods: Patients registered in the Dutch Upper Gastrointestinal Cancer Audit (DUCA) undergoing curative MIE were included. Length of direct postoperative ICU stay was dichotomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In the Netherlands, esophagectomy and gastrectomy patients are generally extubated immediately after surgery. After esophagectomy, protocol length of postoperative ICU stay varies from 0 to 2 days among Dutch hospitals [19]. Standard procedure after gastrectomy is not to admit patients to the ICU.…”
Section: Ancillary Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Netherlands, esophagectomy and gastrectomy patients are generally extubated immediately after surgery. After esophagectomy, protocol length of postoperative ICU stay varies from 0 to 2 days among Dutch hospitals [19]. Standard procedure after gastrectomy is not to admit patients to the ICU.…”
Section: Ancillary Supportmentioning
confidence: 99%
“…16 ( 8) 40 ( 21) 33 ( 17) 54 ( 28) 50 (26) 168 (15) 211 (19) 213 (19) 269 (24) 273 ( 24 yield is lower after surgery late in the week. The current study did display significantly higher 30-day readmission rates after gastrectomy later in the week.…”
Section: Gastric Cancermentioning
confidence: 99%
“… 25 , 26 A nationwide study of minimally invasive esophagectomy in the Netherlands demonstrated great heterogeneity in ICU LOS, pointing to differences in use of early extubation protocols and analgesic modalities as contributing factors. 27 Investigation at a broader scale is necessary to confirm the generalizability of our findings and to identify modifiable practice patterns that increase LOS.…”
Section: Discussionmentioning
confidence: 82%
“…Prolonged ICU LoS refers to a period longer than 2 d (the day of surgery + 1 d) because based on the protocol in our center, a standard ICU stay is 1 or 2 d. A short ICU stay was associated with shorter overall hospital admission time and did not negatively impact short-term surgical outcomes[ 12 ]. Prolonged ICU LoS is a risk factor for mortality[ 2 ].…”
Section: Discussionmentioning
confidence: 99%